Insolvency and bankruptcy based on Islamic principles within China – a data-driven analysis and framework - Katterbauer, Klemens; Syed, Hassan; Genc, Sema Yilmaz; Cleenewerck, Laurent (European Journal of Islamic Finance, 2023)
Islamic bankruptcy law and finance have taken on a growing role in modern economies, with several governments aiming to align the economic system with Islamic principles and solve some of the shortcomings of existing financial regulations related to bankruptcies. Within the last 40 years, China has become a major economy with significant development of its legal system. With the increasing growth and engagement with the Muslim world, challenges have arisen with speculative business practices and rising defaults. Furthermore, the growing engagement with Muslim countries has fostered a growing focus on providing Shariah-compliant legal frameworks to encourage trade and ensure the protection of corporations. Insolvencies and bankruptcies are natural in an economy. However, Islam emphasizes the importance of there being no distinction between balance sheet insolvency and cashflow insolvency, as well as the importance of personal responsibility for the debts incurred. The article has presented a solid outline of the Islamic and Chinese bankruptcy laws and how Islamic principles can be integrated into the Chinese legal system. The arising system in the form of either a separate legal system or one integrating these principles into the existing bankruptcy regulations can significantly strengthen debtor responsibility and recovery rates and encourage fairer business practices.